2022
DOI: 10.3390/ijms232012434
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Evolution, and Expression Pattern Analysis of the GATA Gene Family in Tartary Buckwheat (Fagopyrum tataricum)

Abstract: GATA is a transcription factor that exerts a vital function in plant growth and development, physiological metabolism, and environmental responses. However, the GATA gene family has rarely been studied in Tartary buckwheat since the completion of its genome. This study used bioinformatics methods to identify GATA genes of Tartary buckwheat and to analyze their subfamily classification, structural composition, and developmental evolution, as well as to discuss the expression patterns of FtGATA genes in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
6
8
0
Order By: Relevance
“…Phylogenetic analysis indicated that the GATA proteins from P. ginseng, A. thaliana, and O. sativa were classified into A, B, C, and D groups. This classification is consistent with the grouping of GATA proteins in Setaria italica [64], A. hypogaea L. [66], Populus alba [69], Sorghum bicolor [70], Zea mays L. [71], and Fagopyrum tataricum [72]. Specifically, subgroup A had the highest number of GATAs, and members within the same subgroups exhibited higher sequence similarity.…”
Section: Discussionsupporting
confidence: 83%
“…Phylogenetic analysis indicated that the GATA proteins from P. ginseng, A. thaliana, and O. sativa were classified into A, B, C, and D groups. This classification is consistent with the grouping of GATA proteins in Setaria italica [64], A. hypogaea L. [66], Populus alba [69], Sorghum bicolor [70], Zea mays L. [71], and Fagopyrum tataricum [72]. Specifically, subgroup A had the highest number of GATAs, and members within the same subgroups exhibited higher sequence similarity.…”
Section: Discussionsupporting
confidence: 83%
“…The GATA gene families of tetraploid potato and Arabidopsis share a closer evolutionary relationship than rice. Protein domain analysis showed that the conserved domain of StGATA members in subfamily III was CX 2 CX 20 CX 2 C, whereas that in the other three subfamilies was CX 2 CX 18 CX 2 C. The similar phenomena have been observed in other dicotyledonous plants, such as Arabidopsis ( Reyes et al., 2004 ), soybean ( Zhang et al., 2015 ), and Tartary buckwheat ( Yao et al., 2022 ). However, key differences were observed in the classifications of the GATA subfamily between monocotyledon rice and tetraploid potato.…”
Section: Discussionsupporting
confidence: 64%
“…All duplication events of tetroploid potato were segmental duplication, consisted with that of the wheat GATA gene family ( Feng et al., 2022 ). Segmental duplication events were also dominant in other crops such as grape ( Zhang et al., 2018 ), buckwheat ( Yao et al., 2022 ), and cucumber ( Zhang et al., 2021 ). These reports indicate that segmental duplication events may be the primary mechanism of the expansion of GATA gene family during evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations